Time-lapse imaging of cleavage divisions in embryo quality assessment. Issue 2 (August 2017) - Milewski, Robert; Ajduk, Anna
Abstract : In vitro fertilization (IVF) is one of the most important procedures for treating infertility. As several embryos are usually produced in a single IVF cycle, it is crucial to select only the most viable ones for transfer to the patient. Morphokinetics, i.e. analysis of the dynamics of cleavage divisions and processes such as compaction and cavitation, has provided both biologists and clinicians with a new set of data regarding embryonic behaviour during preimplantation development and its association with embryo quality. In the current review, we focus on biological significance of morphokinetic parameters and show how they can be used to predict a reproductive outcome. We also explain the statistics behind the predictive algorithms and discuss the future perspectives of morphokinetics.